2013
DOI: 10.3892/or.2013.2589
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin increases sensitivity of Hep3B human hepatocellular carcinoma cells to TRAIL-mediated apoptosis by inactivating the JNK signaling pathway

Abstract: Abstract. Resistance to tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced apoptosis has been reported in various cancer cells. Cordycepin, a specific polyadenylation inhibitor, is the main functional component in Cordyceps militaris, which possesses many pharmacological activities including antitumor and anti-inflammation. In the present study, we demonstrated that treatment of cordycepin sensitized TRAIL-resistant Hep3B human hepatocellular carcinoma cells to TRAIL-mediated apoptosis as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Traditional Chinese medicine is one of them for complementary and alternative therapy. Cordycepin, an active compound extracted from one Traditional Chinese medical herb, Cordyceps militaris, has been studied to treat many cancers including lung cancer (50), ovarian cancer (46), leukemia (30), breast cancer (47), brain cancer (19), colon cancer (27), liver cancer (25), and so on (33). Recently, some efforts have been done to investigate the po- PTEN/PI3K/Akt signaling pathway is an important pathway regulated by microRNA-21 (7).…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medicine is one of them for complementary and alternative therapy. Cordycepin, an active compound extracted from one Traditional Chinese medical herb, Cordyceps militaris, has been studied to treat many cancers including lung cancer (50), ovarian cancer (46), leukemia (30), breast cancer (47), brain cancer (19), colon cancer (27), liver cancer (25), and so on (33). Recently, some efforts have been done to investigate the po- PTEN/PI3K/Akt signaling pathway is an important pathway regulated by microRNA-21 (7).…”
Section: Discussionmentioning
confidence: 99%
“…In general, those drugs often anti-metabolites that interfere with nucleic acid or protein synthesis can suppress the immune response. The greatest problem facing the physician is to effectively balance at the same time the dosages of drugs or irradiation so that the immune system is suppressed against the graft, but is still capable of defense against environmental pathogens [32][33][34][35][36][37][38][39][40][41][42].…”
Section: Acquired Immuno-suppressionmentioning
confidence: 99%
“…This result indicated that cordycepin induces tumor cell death through PKC/MAPK signaling pathways. Lee et al (38) performed Western blot analysis, which demonstrated that JNK-inactivating phosphatase was upregulated in response to treatment with cordycepin in human hepatocellular carcinoma Hep3B cells. Thus, according to the results of Pao et al (7) and Lee et al (38), we hypothesize that cordycepin induces cell apoptosis via the activation of PLC/PKC and subsequent inactivation of JNK, which is an important component of the MAPK and downstream PLC/PKC signaling pathways.…”
Section: Cell Apoptosis Induced By Cordycepinmentioning
confidence: 99%
“…Lee et al (38) performed Western blot analysis, which demonstrated that JNK-inactivating phosphatase was upregulated in response to treatment with cordycepin in human hepatocellular carcinoma Hep3B cells. Thus, according to the results of Pao et al (7) and Lee et al (38), we hypothesize that cordycepin induces cell apoptosis via the activation of PLC/PKC and subsequent inactivation of JNK, which is an important component of the MAPK and downstream PLC/PKC signaling pathways. Western blot analysis performed by Chen et al (39,40) also found that 24 h treatment with 10 or 100 µmol/l cordycepin exhibited a synergistically apoptotic effect through the activation of JNK/caspase-7/PARP pathway in human OC3 oral cancer cells.…”
Section: Cell Apoptosis Induced By Cordycepinmentioning
confidence: 99%